If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(y + -3) + y = 12 Reorder the terms: -2(-3 + y) + y = 12 (-3 * -2 + y * -2) + y = 12 (6 + -2y) + y = 12 Combine like terms: -2y + y = -1y 6 + -1y = 12 Solving 6 + -1y = 12 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1y = 12 + -6 Combine like terms: 6 + -6 = 0 0 + -1y = 12 + -6 -1y = 12 + -6 Combine like terms: 12 + -6 = 6 -1y = 6 Divide each side by '-1'. y = -6 Simplifying y = -6
| 5f+2=-4+2f-8 | | 2.75+.003+.158=2.938 | | 9m-2m=77 | | 4g+g=12 | | 3a-2a=12 | | 4xz=2104 | | 700/15 | | 3x+x=1 | | 1/cotu | | 5f+2=-42f-8 | | 2sectheta-2/1-costheta=2sectheta | | n+72=180 | | 6a+9=8 | | 55b^2-155b-30= | | 50/y=y/2 | | Mx=8 | | -31-3p=7+4(8+8p) | | 22+t=72 | | c+(-8+6c)=0 | | 16(4y-5)=8(7y+5) | | 5x-7/3=xx | | 5x-7u/2=2u-; | | -2(x-3)(x+3)-18=0 | | 3(5w-2)-4(3w-5)=w | | 28-x+30-x+3x+x=40 | | -7+6.5(1+2.5s)=-16.5 | | (T+0.5)4=5 | | -6xy+6xy= | | X(2)=5(5) | | f(-2)=(4m-3)/(m-7) | | 2(x-5)=7-2x | | 3sinx-4cosx-2=0 |